The effects of olive meal supplementation on feedlot performance and longissimus muscle fatty acid composition of Wagyu steers and the impact of calcium dose and olive meal on in vitro rumen fermentation characteristics - Tangredi, Briana V., author; Engle, Terry E., advisor; Delmore, Robert J., committee member; Holt, Timothy N., committee member (Colorado State University. Libraries, 2022)
Two experiments were conducted to evaluate the effects of olive meal supplementation on feedlot performance of Wagyu steers and the impact of Ca dose and olive meal on in vitro rumen fermentation characteristics. Experiment 1: Eighty-three American Wagyu steers (725 ±10.7 kg) were used to evaluate the effects of olive meal supplementation on feedlot performance and carcass characteristics. The steers were blocked by BW. The heaviest 8 steers were stratified into two pens containing 3 or 4 steers per pen with similar pen BW. This was considered a paired weight block. This process was repeated until all steers were assigned to pens. Each pen contained 3 or 4 steers/pen with 11 replicates/treatment. Steers were blocked by initial body weight (BW) and randomly assigned within block to one of two treatments. Treatments consisted of: 1) Control (basal ration with no olive meal) + 1 kg of supplemental cracked corn per animal per day, or 2) Control diet + 1 kg of supplemental olive meal per animal per d ay. Steers were housed in feedlot pens (n=4 steers/pen; 11 replicates/treatment) and fed a traditional American Wagyu finishing diet (DM basis: 68.4% DM, 14.3% CP; 74.8% TDN, 1.16 Mcal/kg NEg, 5.3% crude fat). Diets were delivered to pens, once daily, in the morning in amounts to allow ad libitum access to feed over a 24 h period. Olive meal and cracked corn were top-dressed to the appropriate treatment pens immediately after delivery of the basal ration. Steers were individually weighed on d -1 and 0, and approximately every 28 d throughout the 177 d experiment. Equal numbers of steers per treatment were slaughtered throughout the experiment and carcass data were collected. Steers receiving olive meal had a lower final BW, ADG, DMI, and FE (P < 0.05) when compared to steers receiving the control diet. Longissimus muscle C18:1 tended to be greater (P < 0.06) in steers receiving olive meal when compared to controls. Under the conditions of this experiment, feeding olive meal at 1.0 kg/ animal /day reduced live animal performance and had minimal impacts on longissimus muscle fatty acid composition. Experiment 2: Rumen fluid from three beef steers (480 ± 10 kg) fitted with rumen canulae, was used to investigate the impact of Ca dose and olive meal on in vitro rumen fermentation characteristics. Steers were fed a high concentrate finishing diet for 21 d and rumen fluid was collected from each steer 2h post-feeding. A 2 x 4 factorial arrangement of treatments was used for this experiment. Factors included: 1) 0 or 5% olive meal and 2) Ca dose: 0, 0.02, 0.04, and 0.08% Ca from CaCl2. A McDougall's buffer-rumen fluid mixture (1:1; 30 mL 5 total volume) was added to conical tubes containing 0.5g of the ground basal diet with the appropriate treatments and incubated at 39°C for 0, 4, 8, and 12h (5 replicates per treatment per time point). After incubation, supernatant was removed for VFA analysis and the remaining digesta was dried to determine DM disappearance (DMD). There were no olive meal x Ca interactions for any response variables measured. At 4 and 8 h post incubation digestion tubes containing 0.04% Ca had greater (P < 0.001) DMD when compared to all other Ca doses. At 12 h post incubation, DMD was greater (P < 0.001) in digestion tubes containing 0.02% and 0.08% Ca compared to all iv other Ca doses. At 8 h post incubation, molar proportions of acetic acid were greater (P < 0.03) in digestion tubes containing olive meal compared to no olive meal and were greater (P < 0.001) in digestion tubes containing 0.08% Ca compared to all other Ca doses. At 12 h post incubation, iso-butyric acid (P < 0.01) and butyric acid (P < 0.02) were greater in digestion tubes containing 0.02% and 0.04% Ca compared to all other Ca doses. Butyric acid was lesser (P < 0.02) with olive meal inclusion at 12 h. Total VFA concentrations were similar across treatments. These data suggest that Ca and olive meal may impact in vitro fermentation. Dietary treatment was a significant (P < 0.05) source of variation for caproic (C6:0), capric (C10:0), linoleic (C18:2n-6), linolelaidic (C18:2n-6 trans), and docosahexaenoic (C22:6n-3) longissimus muscle fatty acids. Steers receiving the control diet had greater C6:0 (P < 0.02), C10:0 (P < 0.02), C18:2n-6 trans (0.02), and C22:6n-3 (P < 0.05) fatty acids when compared to cattle receiving olive meal. Steers receiving olive meal had greater C18:2n-6 (P < 0.04) when compared to controls. All other fatty acids identified were similar across treatment. Based on these data Ca addition at the concentration supplied in this experiment did not inhibit biohydrogenation of unsaturated fatty acids but did improve fermentation characteristics.
Keywords: beef cattle; carcass characteristics; volatile fatty acids; Japanese Black; Wagyu and dry matter disappearance